2017
DOI: 10.1002/jso.24752
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein territory identification using indocyanine green fluorescence imaging: Technical details and short‐term outcomes

Abstract: We have demonstrated the technical details of five types of fluorescence staining techniques. These techniques are safe to perform and facilitate clear visualization of the PV territory in real time, enhancing the efficacy of anatomical removal of such territories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…To overcome disadvantages in conventional marking methods, we turned to ICG‐mediated imaging, which has been applied in sentinel lymph node navigation and orientation of the liver segments . During sentinel lymph node navigation, ICG is endoscopically injected into the submucosal layer of the stomach, which is similar to our method; several previous studies have reported the safety of this method .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome disadvantages in conventional marking methods, we turned to ICG‐mediated imaging, which has been applied in sentinel lymph node navigation and orientation of the liver segments . During sentinel lymph node navigation, ICG is endoscopically injected into the submucosal layer of the stomach, which is similar to our method; several previous studies have reported the safety of this method .…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Aoki et al showed that such staining was feasible following ultrasound‐guided injection by the intraportal route of 1 ml of ICG (5 mg/ml). Kobayashi et al demonstrated in 2017 the feasibility of portal vein territory identification using ICG with five types of fluorescence staining techniques . In a preclinical study in pigs (data not shown), we determined the volume and the dilution of the ICGp, the lack of interference between preoperative venous injection of ICG and ICGp and the correlation between anatomical fluorescent staining and ischemic staining.…”
Section: Discussionmentioning
confidence: 95%
“…ICG enters hepatocytes from the sinusoid and is excreted into bile. Thus, the technique was reportedly used for hepatobiliary surgery and visualizing liver tumors, bile ducts, hepatic arterial/portal blood flow, and portal and hepatic venous territories. However, two reports demonstrated the visualization of pancreatic lesions, including 13% of pancreatic adenocarcinomas (PDA; n = 1 of 8) and 100% of pancreatic neuroendocrine tumors (NET; n = 10 of 10) …”
Section: Introductionmentioning
confidence: 99%
“…ICG enters hepatocytes from the sinusoid and is excreted into bile. Thus, the technique was reportedly used for hepatobiliary surgery and visualizing liver tumors, 10,11 bile ducts, 12,13 hepatic arterial/portal blood flow, 14 and portal 15,16 and hepatic venous 17,18 territories.…”
Section: Introductionmentioning
confidence: 99%